Electrostatic spraying of imazamox to control the floating aquatic plant Salvinia molesta and its effects on environmental indicators of water quality - Garlich, Nathalia [UNESP]; Garcia, Guilherme Leonardi; Oliveira, Ana Carolina de; Santos, Karina Petri dos; Pitelli, Robinson Antonio; Ferreira, Marcelo da Costa [UNESP]; Cruz, Claudinei da (Taylor & Francis Inc, 2020)
This study aimed to assess, in a microcosm condition, the efficacy of electrostatic spraying of herbicide imazamox in the control of Salvinia molesta and the effects of decomposition of plant material on water quality. The herbicide rates used were 600, 700, 800, and 900 g ai ha(-1) and spray volume of 50 L ha(-1) in electrostatic application. Control effectiveness was assessed at 7, 15, 30, 45, and 60 days after application (DAA), expressed in percentage (0-100%) of visible injury symptoms in the plants, biochemical oxygen demand (BOD5), chemical oxygen demand (COD), chlorophyll a and pheophytin a contents at 0, 7, 15, 30, 45, and 60 DAA, and fresh and dry biomass at 60 DAA. Imazamox was effective in controlling 63% of S. molesta with 900 g ai ha(-1) in 45 DAA and 30% with 800 g ai ha(-1) in 30 DAA, and reduced 82.3% and 17.5% of fresh weight and 62.6% and 9.3% of dry weight of plant at 60 DAA, respectively. The imazamox spray reduced chlorophyll a with all doses applied and increased BOD5 in 45 DAA with 900 g ai ha(-1) and COD in all assessment periods, but for temperature, dissolved oxygen, electrical conductivity, and pH, there was no significant effect after spraying. The herbicide imazamox reduced S. molesta plants with 900 g ai ha(-1), without causing significant effects on environmental indicators of water quality. Electrostatic spraying of herbicide can be used in management strategies of aquatic plants to reduce plant density in water bodies and maintain the colonization of plants at a level not harmful to the aquatic biota.
Keywords: Aquatic environment; efficacy; effectiveness; herbicide; macrophyte; environmental monitoring; spraying technology